HEGEMONI DALAM NOVEL MARYAM KARYA OKKY MADASARI: KAJIAN HEGEMONI GRAMSCI - Dwi Safitri; Siti Fatimah; R. Yusuf Sidiq Budiawan (Universitas Muhammadiyah Surabaya, 2024)
This research aims to describe the hegemony of power in the novel